Enhancing Congruence between Implicit Motives and Explicit Goal Commitments: Results of a Randomized Controlled Trial - Roch, Ramona M.; Rösch, Andreas G.; Schultheiss, Oliver C. (Frontiers in Psychology, 2017)
Objective: Theory and research suggest that the pursuit of personal goals that do not fit a person's affect-based implicit motives results in impaired emotional well-being, including increased symptoms of depression. The aim of this study was to evaluate an intervention designed to enhance motive-goal congruence and study its impact on well-being. Method: Seventy-four German students (mean age = 22.91, SD = 3.68; 64.9% female) without current psychopathology, randomly allocated to three groups: motivational feedback (FB; n = 25; participants learned about the fit between their implicit motives and explicit goals), FB + congruence-enhancement training (CET; n = 22; participants also engaged in exercises to increase the fit between their implicit motives and goals), and a no-intervention control group (n = 27), were administered measures of implicit motives, personal goal commitments, happiness, depressive symptoms, and life satisfaction 3 weeks before (T1) and 6 weeks after (T2) treatment. Results: On two types of congruence measures derived from motive and goal assessments, treated participants showed increases in agentic (power and achievement) congruence, with improvements being most consistent in the FB+CET group. Treated participants also showed a trend-level depressive symptom reduction, but no changes on other well-being measures. Although increases in overall and agentic motivational congruence were associated with increases in affective well-being, treatment-based reduction of depressive symptoms was not mediated by treatment-based agentic congruence changes. Conclusion: These findings document that motivational congruence can be effectively enhanced, that changes in motivational congruence are associated with changes in affective well-being, and they suggest that individuals' implicit motives should be considered when personal goals are discussed in the therapeutic process.